インドネシア語における「Se 」という接頭辞 - Gapur, Abdul; Taulia, Taulia; Pujiono, Mhd. (Universitas Harapan Medan, 2022)
This paper aims to describe the function of the prefix “se-” in Bahasa Indonesia. The approach is qualitative and uses descriptive methods. Data are words that begin with